Penanaman Karakter Kewirausahaan Di TK Alam Al-Azhar Kutai Kertanegara - Wildan Saugi; Iin Sundari; Agustiah Agustiah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
This research aims to find out the implementation of entrepreneurship character building on children at early age at TK Alam Al-Azhar Loa Janan Kutai Kertanegara, the activities carried out to build the entrepreneurship characters, supporting and obstructing factors in the process of the implementation. This research is field research with a qualitative approach. The data collection techniques used observations, interviews, and documentation. The research data was analyzed with the descriptive technique. The result shows that entrepreneurship character building is carried out through the integration of entrepreneurship characters such as discipline, independent, honest, leadership, communicative, creative, hard work, risk-taking, patient, and diligent with daily activities at school. TK Alam also design and implement specific activities related to and aiming to introduce entrepreneurship. Activities at TK Alam Al-Azhar to build entrepreneurship characters are daily habituation activities, schedule of watering plants and feeding fishes, schedule of being imam of Dhuha prayer for male students, family day, peak of theme such as visit, market day, gardening, vegetable harvest, and fishing. Supporting factors are large and fertile soil, natural facilities such as garden and fish pool, cooperation between school and societies, school location at Poros street Samarinda-Balikpapan, and experienced human resources. The obstructing factors are the condition of slope land which is prone to slide, the condition of the pools which are not permanent, the condition of the footpaths to the pools and the garden which are slightly far and slippery after raining, and the plant maintenance which is not routine during a long holiday. Keywords: entrepreneurship character; children at early age; habituationReferences Denzin, N. K., & Lincoln, Y. S. (Eds.). (1994). Handbook of qualitative research. Sage Publications.Fithriyana, R. (2016). Peningkatan Kewirausahaan melalui Pembelajaran dengan Menggunakan Media Budidaya pada Anak Usia Dini di TK Taqifa Bangkinang Kota. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2(2), 26–35.Halimah, Leli. (2016). Pengembangan Kurikulum Pendidikan Anak Usia Dini. PT Refika Aditama.Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71.Krisdayanthi, A. (2018). Menumbuhkan Jiwa Kewirausahaan pada AUD sebagai Bekal Kecakapan Hidup. Jurnal Pratama Widya, 3(2), 20–27.Kurniadi, F. (2015). Peranan Pembangunan Minat Kewirausahaan pada Siswa PAUD dalam Menyambut MEA dengan Model Menjual Karya Sendiri. Research and Development Journal of Education, 1(2), 3–11.Kusumawati, I. (2016). Pengembangan Karakter Siswa Raudlatul Athfal Berbasis Pendidikan Agama Islam. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 139–148.Nadjih, D., & Imroatun. (2016). Hadits Tentang Metode Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa. http:// repository.uinbanten.ac.id/1420/9/09 - Prosiding PGRA - Difla Nadjih.pdfNarwati, S. (2011). Pendidikan Karakter, Pengintegrasian 18 Nilai Pembentuk Karakter dalam Mata Pelajaran. Familia.Nawawi, I. et al. (2005). Syarah dan Terjemah Riyadhus Shalihin (M. et al Dhofir, Trans.). Al-I’tishom.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin: Jurnal Ilmu-Ilmu Keislaman, 9(1), 49–60.Qudsyi, H. (2010). Optimalisasi Pendidikan Anak Usia Dini Melalui Pembelajaran yang Berbasis Perkembangan Otak. Buletin Psikologi, 18(2), 94.Rahman, U. (2009). Karakteristik Perkembangan Anak Usia Dini. Lentera Pendidikan, 12(1), 55.Shofa, M. F. (2017). Kerangka Konsep Pengembangan Kurikulum Berbasis Multiple Intelligence Pada Pendidikan Anak Usia Dini. 2(2), 216.Syifauzakia. (2016). Penanaman Nilai-nilai Kewirausahaan pada Anak Usia dini Melalui Metode Proyek (Penelitian Tindakan Kelas pada Anak Kelas B2 RA Miftahul Falah di Kecamatan Cileunyi Kabupaten Bandung). Jurnal Tunas Siliwangi, 2(1), 92–113.UNICEF. (2019). Learning Through Play: Strengthening Learning Through Play in Early Childhood Education Programmes. UNICEF. https://www.unicef.org/sites/default/files/2018-12/UNICEF-Lego-Foundation-Learning-through-Play.pdf